2018
DOI: 10.1242/jcs.215855
|View full text |Cite
|
Sign up to set email alerts
|

Cell-matrix adhesion controls Golgi organization and function through Arf1 activation in anchorage-dependent cells

Abstract: Cell-matrix adhesion regulates membrane trafficking controlling anchorage-dependent signaling. While a dynamic Golgi complex can contribute to this pathway, its regulation by adhesion remains unclear. Here we report that loss of adhesion dramatically disorganized the Golgi in mouse and human fibroblast cells. Golgi integrity is restored rapidly upon integrin-mediated re-adhesion to FN and is disrupted by integrin blocking antibody. In suspended cells, the cis, cis-medial and trans-Golgi networks differentially… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 102 publications
1
35
0
Order By: Relevance
“…In addition, we observed that miR-30d promotes secretion also by inducing microtubule stability, possibly via indirect effects on kinesins involved in dynamic assembly of Golgi mini-stacks 62,63 .…”
Section: Discussionmentioning
confidence: 82%
“…In addition, we observed that miR-30d promotes secretion also by inducing microtubule stability, possibly via indirect effects on kinesins involved in dynamic assembly of Golgi mini-stacks 62,63 .…”
Section: Discussionmentioning
confidence: 82%
“…Further studies will be required to fully understand how each gene regulates protein secretion. Interestingly, a recent study has shown the importance of the extracellular matrix (ECM) in regulating Golgi organisation and function via the activation of ARF1 27 . MXRA7, a component of the ECM, might play a similar role.…”
Section: Discussionmentioning
confidence: 99%
“…Cell spreading upon adhesion triggers exocytosis of Golgi-derived vesicles delivering lipids required to expand the cell area (Gauthier et al, 2011). Cells in suspension display a fragmented Golgi already few minutes after losing contact with their substrate, a phenomenon that can be rescued by restoring Arf1 activity, which normally occurs downstream of activated integrins (Singh et al, 2018). Integrins are the main adhesion receptors of cells, and this observation suggests that the Golgi responds to a mechanotransduced signal downstream of integrins (Singh et al, 2018).…”
Section: Golgi Apparatusmentioning
confidence: 99%
“…Cells in suspension display a fragmented Golgi already few minutes after losing contact with their substrate, a phenomenon that can be rescued by restoring Arf1 activity, which normally occurs downstream of activated integrins (Singh et al, 2018). Integrins are the main adhesion receptors of cells, and this observation suggests that the Golgi responds to a mechanotransduced signal downstream of integrins (Singh et al, 2018). Intriguingly, Golgi fragmentation in suspended cells was correlated with an increase in glycosylated proteins at the PM which did not depend on newly synthesized proteins, but rather on increased trafficking from the Golgi or increased Golgi-glycosylation activity (Singh et al, 2018).…”
Section: Golgi Apparatusmentioning
confidence: 99%
See 1 more Smart Citation